2010
DOI: 10.1016/j.atherosclerosis.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and prevalence of peripheral artery disease, the National Health and Nutrition Examination Survey, 1999–2004

Abstract: Objectives We sought to determine whether mean platelet volume (MPV) is associated with the prevalence of peripheral artery disease (PAD). Background Platelets play a pivotal role in the pathogenesis of atherosclerosis and PAD. MPV, a measure of platelet size available in every blood count, is increasingly recognized as an important marker of platelet activity. Methods We analyzed data from 6354 participants aged 40 years and older from the 1999 to 2004 National Health and Nutrition Examination Survey (NHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 35 publications
5
91
0
5
Order By: Relevance
“…12,13 Previous studies disclosed that MPV was linked with coronary artery disease, myocardial infarction, peripheral artery disease, and cerebral ischemia. [5][6][7][8] Several studies have showed that there were aggregates of thyrombocytes in retinal capillaries of diabetic rats. 14, 15 Tuzcu et al 9 conducted an experiment with 192 patients and showed a correlation between MPV levels and DR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Previous studies disclosed that MPV was linked with coronary artery disease, myocardial infarction, peripheral artery disease, and cerebral ischemia. [5][6][7][8] Several studies have showed that there were aggregates of thyrombocytes in retinal capillaries of diabetic rats. 14, 15 Tuzcu et al 9 conducted an experiment with 192 patients and showed a correlation between MPV levels and DR.…”
Section: Resultsmentioning
confidence: 99%
“…5 It is a marker indicating subclinical platelet activation and is an independent risk factor for various vascular episodes such as acute myocardial infarction, 5 coronary artery disease, 6 cerebral ischemia, 7 and peripheral artery disease. 8 There are limited reports in literature showing relation between DR and platelet indices. Increased MPV has been found to be associated with increased risk of retinopathy in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…As a meta‐analysis comprising 24 trials demonstrated, MPV is a positively associated with incidence of myocardial infarction as well as restenosis after coronary angioplasty (Chu et al, 2010). Meanwhile, high MPV levels had been found in patients with aortic arterial stiffness, peripheral artery disease (Balta et al, 2014; Berger, Eraso, Xie, Sha, & Mohler, 2010). Previous studies reported that high MPV levels were correlated with increased risk of ischemic stroke as well as unfavorable prognosis among survivors of stroke (Bath, Algert, Chapman, & Neal, 2004; Muscari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…7 In patients with a myocardial infarction or cerebrovascular disease, [7][8][9][10][11][12] platelet volume has been found to be increased, and MPV is independently associated with peripheral artery disease. 13 However, data in mesenteric vascular disease are lacking. Our objective in this study is to discuss the usability of MPV, which is associated with numerous vascular pathologies, in the early diagnosis of AMI.…”
mentioning
confidence: 99%